HC-SR04 Sensor Implementation in an IoT-Based Fresh Fruit Bunch Filling Prototype for Vertical Sterilizer - Selamat Meliala; Yogi Satya; Rosdiana Rosdiana; Muhammad Daud; Taufiq Taufiq (Faculty of Engineering, Malikussaleh University, 2024)
This study develops an IoT-based Fresh Fruit Bunch (FFB) filling prototype for vertical sterilizers using the HC-SR04 ultrasonic sensor to enhance the accuracy and efficiency of the filling process in palm oil mills. The system incorporates a non-contact distance sensor to ensure precise measurement and integrates IoT technology and a Telegram bot for real-time monitoring and automation. Testing results indicated that the HC-SR04 sensor achieved high accuracy, maintaining a low tool failure rate of 0.036%, making it highly reliable for industrial applications. Visual and audio indicators, including LEDs and buzzers, were used to enhance user awareness and safety during the filling process. By automating and optimizing FFB loading, the system minimizes operational inefficiencies commonly associated with manual filling methods and improves safety by reducing human intervention. These findings suggest that the developed prototype can provide significant operational benefits to the palm oil industry and other sectors requiring similar improvements in productivity and sustainability. Future research will focus on refining the prototype and evaluating its scalability for broader industrial use.